MELIOIDOSIS : A Hidden Danger Beneath Our Feet - Yuwana, Podin (UNIMAS Publisher, 2025)
Melioidosis is a serious disease caused by a bacterium found in soil and water, called Burkholderia pseudomallei. It can infect both humans and animals. The illness was first recognized in Rangoon in 1912 as a condition that looked like glanders, a disease in horses and donkeys. A year later, an outbreak struck laboratory animals in Kuala Lumpur. By 1921, it was named “melioidosis” because of its similarity to donkey glanders.